2008
DOI: 10.1097/mrr.0b013e3282f45225
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical profiles in Turkish children with cerebral palsy: analysis of 625 cases

Abstract: The aim of the study was to investigate risk factors, clinical profiles and gross motor function levels of Turkish children with cerebral palsy (CP). A total of 625 consecutive children with CP, who were rehabilitated in the pediatrics rehabilitation clinic between 2000 and 2004 years, were included. Factors causing CP were investigated by interviewing the families and by scanning medical files. Risk factors were recorded as consanguineous marriage, maternal disorder, preterm birth, birth asphyxia, low birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 15 publications
3
35
0
12
Order By: Relevance
“…The results of the study showed that 47.7% of cases versus 24.2% of controls were from consanguineous parents (1st or 2nd cousins) and this was an important variable remaining in the regression model (OR = 4.62; 95% CI: 2.07-10.3). In other published research consanguinity was also found to be among the top risk factors (8). The results of our study provides some evidence of a genetic etiology for cerebral palsy.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The results of the study showed that 47.7% of cases versus 24.2% of controls were from consanguineous parents (1st or 2nd cousins) and this was an important variable remaining in the regression model (OR = 4.62; 95% CI: 2.07-10.3). In other published research consanguinity was also found to be among the top risk factors (8). The results of our study provides some evidence of a genetic etiology for cerebral palsy.…”
Section: Discussionsupporting
confidence: 65%
“…A study in Palestine found higher reading disabilities in children with consanguineous parents (6,11). However, other risk factors of importance for cerebral palsy in the region have been suggested, such as hypoxia, low birth weight, jaundice and preterm birth (8,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serdaroglu et al (4) reported that the most common spastic subtype in their sample was diplegia (39.8%), followed by hemiplegia (28.0%). A study conducted in Ankara by Erkin et al (5) found that hemiplegia was the third most common subtype of spasticity, with a proportion of 12.8% of patients. However, a Swedish study conducted by Hagberg (12) found that 44% of 241 patients with CP were diplegic and 33% was hemiplegic.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CP was determined as 4.4 per 1000 live births in Turkey (4,5). Istanbul is home to 17% of the Turkish population and is the largest city in Turkey (12,915,158 people in 2009) (6).…”
Section: Introductionmentioning
confidence: 99%